2014
DOI: 10.2134/agronj13.0487
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Improvement in Maize Yield and Nitrogen Use Efficiency with Integrated Agronomic Management Strategies

Abstract: Low nitrogen use efficiency (NUE) and productivity with excessive use of N fertilizer in maize (Zea mays L.) is a common issue for smallholder farm systems. A 2-yr field study was conducted to assess the impacts of integrated agronomic management strategies (MT) on pre-and post-silking N uptake, dry matter (DM) production dynamics, and their relationships to yield and NUE components. Three MTs were compared with the regional conventional farming practices (FP). We found that biomass yields differed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Compared to the oldest era studied (1960), there was a large increase in NUE with the most recent era (2000). This indicates a considerable advancement in corn hybrid ability to use applied N to produce plant biomass and grain, which is consistent with results reported by other studies (Moll et al, 1982;McCullough et al, 1994;Coque and Gallais, 2007;Wang et al, 2014). The mean apparent NRE across N rates was 0.71 for the 2000 era, however, NRE was not greatly different and not highest for the most recent eras at the N rate near the AONR for each era (NRE mean 0.48 ∆kg kg -1 across eras at the NRE nearest the AONR for each era).…”
Section: Nitrogen Use Efficiencysupporting
confidence: 92%
“…Compared to the oldest era studied (1960), there was a large increase in NUE with the most recent era (2000). This indicates a considerable advancement in corn hybrid ability to use applied N to produce plant biomass and grain, which is consistent with results reported by other studies (Moll et al, 1982;McCullough et al, 1994;Coque and Gallais, 2007;Wang et al, 2014). The mean apparent NRE across N rates was 0.71 for the 2000 era, however, NRE was not greatly different and not highest for the most recent eras at the N rate near the AONR for each era (NRE mean 0.48 ∆kg kg -1 across eras at the NRE nearest the AONR for each era).…”
Section: Nitrogen Use Efficiencysupporting
confidence: 92%
“…Smil (2002) estimated that N-based fertilizer has contributed by approximately 40% to the increases in production of main crops in the past 50 years but that large increase in inorganic fertilizer inputs without a correspondingly large increase in yields further decreased the already low agronomic nutrient use efficiency (ratio of grain harvested to applied fertilizer), especially in developing countries ( Fig. 3; Peng et al, 2010;Chen et al, 2011;Wang et al, 2014). In recent years, it has been estimated that twice as much inorganic fertilizer N and P are applied than recovered in crops, and this nutrient imbalance contributes to environmental pollution, which is becoming increasingly severe in rapidly developing countries (Zhang et al, 2012).…”
Section: Organic Fertilizer Represents a Priority For Inmmentioning
confidence: 99%
“…The apparent periodic contribution was calculated by dividing the DM, N or P accumulated during each specific period by the total DM, N or P in plant shoots (the term "shoots" refers here in a botanical sense to the entire aerial portion of the plants) at PM. Nitrogen and P utilization parameters, including N partial factor productivity (PFPn), P harvest index (PHI), and P utilization efficiency (PutE), were calculated according to a similar method described in Chamorro et al (2002) and Wang et al (2014):…”
Section: Plant Sampling and Analysismentioning
confidence: 99%
“…Some studies showed significant increases in both DM and yield with split N application as compared with equivalent preplant applications (Hocking and Mason 1993;Hocking et al 1997;Ma et al 2015), while others (Tayor et al 1991;Cheema et al 2001) reported that split applications of N with a portion at seeding and another at the rosette stage were no more effective in DM and yield than all N applied at seeding. Given the high N rate is usually accompanied with low NUE and not necessarily a high seed yield (Grant and Bailey 1993; Ma and Herath 2016), plus contradictory findings with split N application, a better understanding of the underlying changes in seasonal DM and N accumulation and utilization in grain formation is important to concurrently improve seed yields and NUE (Hocking et al 1997;Ma and Dwyer 1998;Wang et al 2014). However, almost all of such studies on canola have been done on western Canada prairie soils.…”
Section: Introductionmentioning
confidence: 99%